“Influence Of Supplementary Cementitious Materials On Concrete Strength, Durability & Also Impact On Carbon Foot Print” - Prasad, Mr. Phani Bhushan; Anshumali, Dr. (Migration Letters, 2023)
Background: The global warming is one of the major concern of entire world nowadays due to increased carbon foot print level. The increase in carbon foot print is mainly due to industrial pollution, continuous deforestation for urbanization & also due to poor disposal method of industrial waste like fly ash of thermal power plant. Moreover, cement industries are alone responsible for 8% anthropogenic CO2 to the atmosphere. Objective: To reduce carbon foot print in environment by reducing the cement consumption in construction industries by using of SCM (Supplementary Cementitious Materials) at various proportion in concrete as a partial replacement of OPC. This research work involved the comparative studies of various types SCM based concrete with only OPC based concrete for both mechanical strength and durability parameters of concrete. Methods: The experimental procedure involved in the research work comprising of two part like mechanical strength evaluation & durability performance analysis. For mechanical strength evaluation compressive strength & flexural strength of concrete has worked out, while for durability performance o[1]f concrete test like RCPT, ERT, Sorptivity test and Water Permeability test has been conducted. The reduction in cement consumption by using alternate supplementary cementitious materials like fly ash, silica fume etc. as a partial replacement of OPC in concrete is one of the best choice method globally accepted. Results: As per the experimental outcome, it has been observed that concrete with partial replacement of OPC by using SCM like fly ash and silica fume shows significantly higher strength of concrete & also better durability performance than concrete with only OPC. However, the experiment has also shows that on combination of both fly ash & silica fume shows even better strength & durability performance than using of individual SCM like either fly ash or silica fume. The experimental results also show that on adding fly ash up to 15% the workability of concrete increases due to ball bearing effect of spherical sizes fly ash, however on further increase in fly ash % the workability got decreases due to increase in surface area of fines in concrete. The results of fresh concrete also show that on adding of silica fume up to 5% shows improvement in workability, however on 10% it shows reduction in workability due to increased fines in concrete. Conclusion: The experimental results show that using of SCM in concrete as a partial replacement of OPC in concrete as a combined form like fly ash and silica fume shows significant improvement in mechanical strength of concrete and durability performance of concrete with a significant reduction in carbon foot print. In general 1 MT of cement production involved for almost 1 MT of CO2 to the atmosphere, so 25% OPC reduction in concrete is simply reduce the carbon foot print by 25% of cement industries generated CO2 contribution. Thus by promoting the use of SCM in concrete as a partial replacement of OPC mitigate the disposal issue of the waste & also it helps to reduce the carbon foot print contribution of cement industries. Thus by reducing the OPC consumption in concrete through using of SCM shows significant reduction of carbon foot print along with significant improvisation of concrete strength & durability performance.